Pewarisan Bunyi Etimon-etimon Proto-Austronesia dalam Bahasa Karo - Apulina Purba, Maria; Arnati, Ni Wayan (Humanis; Vol 21 No 1 (2017)DO - 10.24843/JH.2017.v21.i01.p22, 2017)
Through this research we get the sounds between Proto-Austronesian language and Karo language as detailed below. First some PAN sounds that remain linearly inherent in the BK are vowel sounds: */i/ and /?/ in each distribution (beginning, middle, and end), consonant: */p/, */b/, */d/,  */c/,*/r/ in each distribution (beginning, middle, and end). Both PAN sounds are inherited; The inheritance of PAN vowels is found as follows. PAN */u/ corresponds /i/, /?/, /a/, /o/ and /h/ in BK, PAN */e/ corresponds /?/, /i/ and /a/ in BK, PAN */a/ corresponds /?/ and /u/ to BK. The consonant inheritance of PAN was found as follows. PAN */t/ corresponds BK /k/ and /l/, PAN */k/ corresponds BK /g/ and /c/, PAN */g/ corresponds BK /h/, PAN */q/ corresponds  /h/, /k/, and  /Ø/, PAN */s/  corresponds BK /n/, PAN * /h/ corresponds BK /d/, PAN */z/ corresponds BK /j/ and /s/, PAN */m/ corresponds BK /p/ and /Ø/, PAN */n/ corresponds BK /?/, /l/, /N/ and /?/, PAN */?/ corresponds BK /d/ and /l/, PAN */l/ corresponds BK /k/, /r/ and /s/. PAN */R/ corresponds BK/l/ and /k/, PAN */w/ corresponds BK /b/, PAN */y/ corresponds BK /r/, diphthong PAN */ay/ becomes monophthong BK /i/ end, diphthong PAN */ey/ becomes monophthong BK /?/ and /a/ at the end position, diphthong PAN * /uy/ becomes monophthong BK /u/ in middle position. The third is found inheritance of several PAN types in BK namely, aferesis, syncope, apocope, protesis, dissimilation, paragog, and epentesis.